Loss of GM-CSF signalling in non-haematopoietic cells increases NSAID ileal injury. Issue 8 (28th June 2010) - Han, Xiaonan; Gilbert, Shila; Groschwitz, Katherine; Hogan, Simon; Jurickova, Ingrid; Trapnell, Bruce; Samson, Charles; Gully, Jonathan
Abstract : Background: Administration of granulocyte-macrophage colony stimulating factor (GM-CSF) relieves symptoms in Crohn's disease (CD). It has been reported that reduced GM-CSF bioactivity is associated with more aggressive ileal behaviour and that GM-CSF-null mice exhibit ileal barrier dysfunction and develop a transmural ileitis following exposure to non-steroidal anti-inflammatory drugs (NSAIDs). STAT5 signalling is central to GM-CSF action. It was therefore hypothesised that GM-CSF signalling in non-haematopoietic cells is required for ileal homeostasis. Methods: Bone marrow (BM) chimeras were generated by reconstituting irradiated GM-CSF receptor ( gm-csfr ) β chain or GM-CSF ( gm-csf ) deficient mice with wild type BM (WTBM→GMRKO and WTBM→GMKO). Intestinal barrier function and the response to NSAID-induced ileal injury were examined. Expression of gm-csf, gm-csfr or stat5 in Caco-2 and HT-29 intestinal epithelial cell (IEC) lines was knocked down and the effect of GM-CSF signalling on IEC survival and proliferation was determined. Results: Elevated levels of GM-CSF autoantibodies in ileal CD were found to be associated with dysregulation of IEC survival and proliferation. GM-CSF receptor-deficient mice and WTBM→GMRKO chimeras exhibited ileal hyperpermeability. NSAID exposure induced a transmural ileitis in GM-CSF receptor-deficient mice and WTBM→GMRKO chimeras. Transplantation of wild type BM into GM-CSF-deficient mice prevented NSAID ileal injury and restored ileal barrier function. Ileal crypt IEC proliferation was reduced in WTBM→GMRKO chimeras, while STAT5 activation in ileal IEC following NSAID exposure was abrogated in WTBM→GMRKO chimeras. Following knock down of gm-csf, gm-csfr α or β chain or stat5a/b expression in Caco-2 cells, basal proliferation was suppressed. GM-CSF normalised proliferation of Caco-2 cells exposed to NSAID, which was blocked by stat5a/b RNA interference. Conclusions: Loss of GM-CSF signalling in non-haematopoietic cells increases NSAID ileal injury; furthermore, GM-CSF signalling in non-haematopoietic cells regulates ileal epithelial homeostasis via the STAT5 pathway. The therapeutic use of GM-CSF may therefore be beneficial in chronic ileitis associated with CD.